A corpus analysis of rubato in Bach's C major prelude, WTC I - Benadon, Fernando (2015)
We  examined  microtiming  properties  in  a  corpus  of  48  recorded  performances  of  J.S.  Bach's  C Major  Prelude  from  The Well  Tempered  Clavier,  Book  I.  Drawing  on  the  results  of  a  listening  experiment  and  from  wavelet  analysis, we derived  a quantitative measure of  rubato  'depth'  that was used  to  assess  timing  trends  across performances.  In  addition  to highlighting  important  structural moments  in  the  Prelude,  rubato was used  to bring melodic  elements  into relief as well as to generate grouping segmentations that may contradict the  Prelude's  inherent  phrase  structure. We  then  applied  the  statistical method  of  principal  components  analysis  (PCA)  to  examine  timing  contours  specific  to  individual performers. Repetitively consistent microrhythmic patterns, which we  qualified  as  groove-like,  differed  from  non-consistent  and  non-repetitive  timing  inflections, which we qualified as rubatoSlike.